A review of the interaction of medicinal plants and arbuscular mycorrhizal fungi in the rhizosphere - Rui-Ting SUN; Ze-Zhi ZHANG; Nong ZHOU; A.K. SRIVASTAVA; Kamil KUČA; Elsayed F. ABD-ALLAH; Abeer HASHEM; Qiang-Sheng WU (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2021)
Medicinal plants are well known to have the advantages of high concentration of medicinal ingredients having clinical importance, curative value, small toxic and side effects. Important compounds viz., paclitaxel, camptothecin, and vincristine have been developed from medicinal plants as first-line of clinical drugs, leading to their consistently increasing demand globally. However, the destruction of natural environment due to excessive mining threatened such resources jeopardizing the successful growing of medicinal plants. A group of beneficial arbuscular mycorrhizal (AM) fungi is known to exist in the rhizosphere of medicinal plants, which can establish a reciprocal symbiosis with their roots, namely arbuscular mycorrhizas. These AM fungi are pivotal in the habitat adaptation of medicinal plants. Studies have demonstrated that AM fungi aided in growth promotion and nutrient absorption of medicinal plants, thereby, accelerating the accumulation of medicinal ingredients and aiding resistance against abiotic stresses such as drought, low temperature, and salinity. An AM-like fungus Piriformospora indica is known to be cultured in vitro without roots, later showed analogous effects of AM fungi on medicinal plants. These fungi provide new mechanistic pathways towards the artificial cultivation of medicinal plants loaded with ingredients in huge demand in international market. This review provides an overview of the diversity of AM fungi inhabiting the rhizosphere of medicinal plants, and analyzes the functioning of AM fungi and P. indica, coupled with future lines of research.